1979
DOI: 10.1007/bf00444347
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA-A1, B8 in children with extrinsic asthma and IgA deficiency

Abstract: The tissue types, immunoglobulin levels, and the presence of circulating autoantibodies were investigated in 57 children. Fifteen of these children suffered from bronchial asthma and, in addition, had no or very little IgA in their serum and saliva (Group 1 patients). Another fifteen children with asthma but normal immunoglobulin levels in serum and saliva (Group 2 patients), seven patients with selective IgA deficiency but without allergic diseases (Group 3 patients), and twenty healthy children served as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The same haplotype was also associated with asthmatic children with an IgA deficiency [24] and nasal polyposis [30]. An increased frequency of Bw6 among patients with nonallergic asthma was also reported, suggesting an association with a recessive inheritance model.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The same haplotype was also associated with asthmatic children with an IgA deficiency [24] and nasal polyposis [30]. An increased frequency of Bw6 among patients with nonallergic asthma was also reported, suggesting an association with a recessive inheritance model.…”
Section: Introductionmentioning
confidence: 85%
“…The human leukocyte antigen (HLA) system has been indicated as a genetic factor that may be associated with the disease. The first studies described in the literature that addressed the association between asthma and the HLA system were performed with HLA class I [23,24,25,26,27] and subsequently with HLA class II [28,29] genes. Different criteria were used to characterize the patients in the studied populations, and their asthma phenotypes were not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular typing of the selected HLA classes I and II allelic groups was performed by polymerase chain reaction using sequence‐specific primers (PCR‐SSP). We studied the allelic groups which have been reported previously to be associated with childhood asthma in various populations . The primer sequences of HLA class I allelic groups were taken from Bunce et al and of class II allelic groups were obtained from Zhu et al and Sacchetti et al .…”
Section: Characteristics Of Asthmatic and Control Subjectsmentioning
confidence: 99%
“…Initial MHC studies demonstrated an association between IgA-D and the class I alleles HLA-A1 -A2 and -B8 (2,3). Subsequent studies reported associations with several class I and I1 alleles, including HLA-A1, -A28, -B8, -B40, -DR3 and -DR7 (4)(5)(6).…”
mentioning
confidence: 99%